The Transformation of Chinese Only-child Parents in Empty-nests - Fujuan Tan (Adult Education Research Conference, 2017)
This qualitative research investigates the transformation of Chinese only-child parents in empty-nests through attending cultural activities in the Chinese community, when their only children leave home and become independent.
Keywords: Chinese only-child parents; Transformation; Human development